2020
DOI: 10.3389/fnbeh.2020.00146
|View full text |Cite
|
Sign up to set email alerts
|

What Does Temporal Brain Signal Complexity Reveal About Verbal Creativity?

Abstract: Recent empirical evidence reveals that creative idea generation builds upon an interplay of multiple neural networks. Measures of temporal complexity yield important information about the underlying mechanisms of these co-activated neural networks. A few neurophysiological studies investigated brain signal complexity (BSC) during the production of creative verbal associations and resting states, aiming to relate it with creative task performance. However, it is unknown whether the complexity of brain signals c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Importantly for the aims of the present study, Kaur et al (2020) showed that BSC, as indexed by MSE, was higher in those neural states in which individuals were asked to produce unusual, creative (as opposed to usual), fluent verbal associations. This was the first evidence to prove BSC as a neural state marker of creative verbal associations.…”
Section: Brain Signal Complexity (Bsc) As a Neural Marker Of Creative...mentioning
confidence: 58%
See 3 more Smart Citations
“…Importantly for the aims of the present study, Kaur et al (2020) showed that BSC, as indexed by MSE, was higher in those neural states in which individuals were asked to produce unusual, creative (as opposed to usual), fluent verbal associations. This was the first evidence to prove BSC as a neural state marker of creative verbal associations.…”
Section: Brain Signal Complexity (Bsc) As a Neural Marker Of Creative...mentioning
confidence: 58%
“…Generally, in line with Benedek et al (2014), we expect that inhibition would partly account for the creative thinking-intelligence relationship at the behavioral level. Furthermore, a previous study (Kaur et al 2020) has shown that the MSE in different task conditions of verbal creativity (i.e., during productions of original vs. typical associations in a verbal DT task) were different on average but were highly correlated. However, different task types (e.g., creative thinking vs. inhibition) involve different mental operations, and signal complexity during such task states is expected to show weaker relationships.…”
Section: Aims Of the Studymentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, we leave open the quest to further explore the human brain, directly tapping the corresponding relations between imagination, memory, emotions, and user specific understanding of complexity based on own background, the stock of knowledge, and previous experiences [81], which influence the reasoning, perception, and understanding of complexity, and further integrate the contributing top-down mechanisms in a vast model of complexity assessment. In terms of image complexity measures, since color entropy and color fractal dimension are not the only measures for describing texture complexity [82][83][84][85][86], measures, like lacunarity (which measures the gaps distributions [87]), succolarity (which expresses the degree of filaments that allow percolation or flow through the texture [88,89]), and artistic complexity derived from neuroscience [84] could be further used for comparison.…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%